2011
DOI: 10.1371/journal.pone.0024185
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Assessment of Exploration and Novelty Seeking in the Human Behavioral Pattern Monitor in Bipolar Disorder Patients and Healthy Individuals

Abstract: BackgroundExploration and novelty seeking are cross-species adaptive behaviors that are dysregulated in bipolar disorder (BD) and are critical features of the illness. While these behaviors have been extensively quantified in animals, multivariate human paradigms of exploration are lacking. The human Behavioral Pattern Monitor (hBPM), a human version of the animal open field, identified a signature pattern of hyper-exploration in manic BD patients, but whether exploratory behavior changes with treatment is unk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
38
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 33 publications
12
38
1
Order By: Relevance
“…Interestingly, novel stimuli induce significantly more activation in the parietal region (Arbabshirani et al 2012), and this region also shows greater synchronous activity with the DMN found in BP relative to SZ and NC (Ongür et al 2010). Given this pair of results, the robust increase in beta power at rest observed in our study may indicate that BP are more responsive to novel stimuli in the environment, an effect that corresponds to recent findings (Minassian et al 2011). Importantly, that mania symptoms predicted beta power in BP in our study suggests that perhaps these symptoms are driven by erratic oscillations between internal trains of thought and distraction by novel stimuli.…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, novel stimuli induce significantly more activation in the parietal region (Arbabshirani et al 2012), and this region also shows greater synchronous activity with the DMN found in BP relative to SZ and NC (Ongür et al 2010). Given this pair of results, the robust increase in beta power at rest observed in our study may indicate that BP are more responsive to novel stimuli in the environment, an effect that corresponds to recent findings (Minassian et al 2011). Importantly, that mania symptoms predicted beta power in BP in our study suggests that perhaps these symptoms are driven by erratic oscillations between internal trains of thought and distraction by novel stimuli.…”
Section: Discussionsupporting
confidence: 90%
“…Previously, we observed a consistent pattern of increased activity, increased exploration, and more linear patterns of movement in mice administered GBR12909 or DAT KD mice in the mouse BPM (Perry et al 2009; Young et al 2010a; b), mimicking the behavior of manic (Minassian et al 2011) and euthymic BD patients (Henry et al 2013). In the current studies, GBR12909 at 13 mg/kg again produced this mania-like behavior in mice.…”
Section: Discussionsupporting
confidence: 60%
“…Previously, we demonstrated that mice with reduced dopamine transporter (DAT) functioning model exploratory profiles of BD mania (Perry et al 2009). Both DAT knockdown (KD) mice and mice receiving the selective DAT inhibitor GBR12909 exhibit hyperactivity, increased exploration, and straight paths of movement as quantified by the mouse behavioral pattern monitor (BPM) (Young et al 2010a; b) similar to patients with BD mania (Minassian et al 2011; Perry et al 2010) and euthymia (Henry et al 2013) in a human BPM. Although some of the abnormal behavior observed in these GBR12909-treated mice, such as impaired decision-making (van Enkhuizen et al 2013b), is also present in depressed patients with BD performing similar human tasks (Adida et al 2011), their hyperactivity, increased motivation (Young and Geyer 2010), and reduced immobility times in the tail suspension test (TST) (Sarkisyan et al 2010) and FST (Esumi et al 2013) more closely model the manic phase of BD.…”
Section: Introductionmentioning
confidence: 99%
“…Under normal housing conditions, the heteroplasmic mice had reduced food intake, spontaneous activity levels, and metabolic rates during the dark cycle (Etain et al, 2011). However, under stressful conditions, the heteroplasmic mice were more excitable and resistant to despair (Flaisher-Grinberg et al, 2010; Gindre and Swendsen, 2010; Minassian et al, 2011). The heteroplasmic mice also showed impaired spatial learning and retention.…”
Section: Discussionmentioning
confidence: 99%